Comparative Analysis of Compressive Strength of Bamboo Leaf Ash and Baggash Ash Concretes - Onikeku, Oluwaseye; Shitote, Stanley Muse; Mwero, John; Adedeji, Adeola. A. (Machakos University, 2019)
Billions tons of conventional concrete are produced yearly as well as cement which emit large tons of carbon dioxide due to huge millions of metric tons produced annually. Sequel to this, there is need to produce a sustainable product due to pollutions from cement production, using agricultural waste materials which have recently been found to be of great interest to construction industries at large due to their ability to substituting cement will solve environmental and pollution related issues. Bamboo leaf ash and baggash ash are produced as a result of combustion which serves as supplementary cementitious materials and can be used for construction purposes. This study determines the compressive strength of concrete without ashes, bamboo leaf ash, and baggash ash concrete at varying percentage replacement of 5%, 10%, 15%, 20% respectively. Physical test, workability test, compressive strength test, and durability test was performed on concretes. A total of 138 cubes were produced using 100*100*100 size cube cured at 7, 28, 56 and 90 days, of which 108 cubes were to ascertain compressive strength for all the concretes, while 30 cubes were used for durability test. Based on experimental results obtained, BLA surpassed BA concrete, and concrete without ash in term of compressive strength at early and later age of curing using 10% as optimum level of replacement, thus, one way ANOVA indicated, that BLA concrete is statistically better than BA concrete and statistically the same at 56 and 90 days of curing for conventional, BLA, and BA concrete. Furthermore, BLA and BA concretes reduced durability. BA concrete increased the water absorption, permeable voids, and sorptivity. As a result, BLA and BA can be considered as a good pozzolanic material which can save cost of construction, improved concrete properties
Keywords: Concrete; Physical Test; Compressive Strength; Durability Test; Bamboo Leaf Ash; Baggash Ash; One – Way ANOVA